A Novel Mapping System for Panoramic Mapping of the Left Atrium: Application to Detect and Characterize Localized Sources Maintaining Atrial Fibrillation - Honarbakhsh, Shohreh (JACC Clin Electrophysiol, 2018)
OBJECTIVES: This study sought to use a novel panoramic mapping system (CARTOFINDER) to detect and characterize drivers in persistent atrial fibrillation (AF). BACKGROUND: Mechanisms sustaining persistent AF remain uncertain. METHODS: Patients undergoing catheter ablation for persistent AF were included. A 64-pole basket catheter was used to acquire unipolar signals, which were processed by the mapping system to generate wavefront propagation maps. The system was used to identify and characterize potential drivers in AF pre- and post-pulmonary vein (PV) isolation. The effect of ablation on drivers identified post-PV isolation was assessed. RESULTS: Twenty patients were included in the study with 112 CARTOFINDER maps created. Potential drivers were mapped in 19 of 20 patients with AF (damage to the basket and noise on electrograms was present in 1 patient). Thirty potential drivers were identified all of which were transient but repetitive; 19 were rotational and 11 focal. Twenty-six drivers were ablated with a predefined response in 22 of 26 drivers: AF terminated with 12 and cycle length slowed (≥30 ms) with 10. Drivers with rotational activation were predominantly mapped to sites of low-voltage zones (81.8%). PV isolation had no remarkable impact on the cycle length at the driver sites (138.4 ± 14.3 ms pre-PV isolation vs. 137.2 ± 15.2 ms post-PV isolation) and drivers that had also been identified on pre-PV isolation maps were more commonly associated with AF termination. CONCLUSIONS: Drivers were identified in almost all patients in the form of intermittent but repetitive focal or rotational activation patterns. The mechanistic importance of these phenomena was confirmed by the response to ablation.